2014
DOI: 10.1136/heartjnl-2014-305576
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation in adults with congenital heart disease: The who, the when and the how?

Abstract: Adults with congenital heart disease are a growing population. One of the major challenges in the care of these patients is to prevent thromboembolic episodes. Despite relative young age and no typical cardiovascular risk factors, this cohort has a high prevalence of thrombotic events. It is difficult to use treatment algorithms from the general adult population with acquired heart disease in this heterogeneous population due to special conditions such as myocardial scarring after previous surgery, atypical at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 32 publications
(43 reference statements)
0
36
0
3
Order By: Relevance
“…Ponadto leczenie przeciwzakrzepowe u dorosłych pacjentów z wrodzoną wadą serca, u których występują tachyarytmie przedsionkowe, należy rozważać w przypadku przebytej wewnątrzsercowej operacji naprawczej, występowania sinicy, stanu po leczeniu paliatywnym z wytworzeniem krążenia typu Fontana, a także systemowej prawej komory [968]. Można stosować beta--adrenolityki, werapamil, diltiazem oraz naparstnicę.…”
Section: Ogólne Zasady Leczenia Tachyarytmii Przedsionkowych U Dorosłunclassified
“…Ponadto leczenie przeciwzakrzepowe u dorosłych pacjentów z wrodzoną wadą serca, u których występują tachyarytmie przedsionkowe, należy rozważać w przypadku przebytej wewnątrzsercowej operacji naprawczej, występowania sinicy, stanu po leczeniu paliatywnym z wytworzeniem krążenia typu Fontana, a także systemowej prawej komory [968]. Można stosować beta--adrenolityki, werapamil, diltiazem oraz naparstnicę.…”
Section: Ogólne Zasady Leczenia Tachyarytmii Przedsionkowych U Dorosłunclassified
“…Of note, this and the HAS-BLED score have not been evaluated in patients with ACHD. Their applicability and potential benefit in these patients is uncertain, but at this time there is no better instrument for risk stratification available and its application is therefore recommended in current guidelines 23. Recently, a study evaluated thrombotic and bleeding events in 229 patients with ACHD 24.…”
Section: Acute Treatment Of Svt In Achdmentioning
confidence: 99%
“…The authors evaluated dichotomized CHA2-DS2-VASc and HAS-BLED scores in their ACHD cohort and reported that thrombotic and bleeding events can be predicted by using scoring systems[97]. In moderate/complex patients with IART or AF, long-term oral anticoagulation is recommended with vitamin K antagonist (VKA) however, in simple nonvalvular CHD, the decision of anticoagulation risk can be guided by CHA2DS2-VASc score[17,98]. Patients with CHA2DS2-VASc score of ≥ 2 need oral anticoagulation with VKA or novel oral anticoagulants[17].…”
Section: Management Of Chronic or Recurrent Atrial Arrhythmias In Achmentioning
confidence: 99%